PENGARUH HEALTH EDUKASI BERBASIS TELENURSING TERHADAP PENINGKATAN PENGETAHUAN DAN KEMAMPUAN PASIEN COVID-19 DALAM MELAKSANAKAN PERAWATAN MANDIRI DIRUMAH - Sjattar, Elly Lilianty; Majid, Abdul; Arafah, Rosyidah; Syam, Yuliana; Gaffar, Indra; Harisa, Akbar (Jurnal Kesehatan, 2022)
Corona Virus Disease-2019 (Covid-19) is an infectious disease caused by a new type of coronavirus, namely SARS-CoV-2. In the beginning of 2020 WHO had declared a global pandemic for this disease and many infected had no symptoms or were mild so they needed isolation, on the other hand there were still many people who didn’t knor about how to self-isolate at home which impacted in the higher transmission rate. This study was aimed to determine the increase in knowledge and abilities of Covid-19 patients regarding care during self-isolation at home. This research is a quantitative study with a pre-experimental approach using purposive sampling technique, the sample in this study were 47 patients who were confirmed positive for Covid-19 who were carrying out self-care at home, willing to be respondents. Health education is carried out using an online method via whatsapp (WA) with booklet media. Data was collected using a questionnaire that had been tested for validity and reliability. Statistical test using t-test. The study showed that there was a significant increase in the knowledge and ability of Covid-19 patients after being given health education about self-care at home. Providing health education online through WA to Covid-19 patients can increase their knowledge and abilities. This research is expected to provide additional information about the health education of Covid-19 patients, especially those who are carrying out self-isolation. For further researchers, in order to examine other variables, such as psychosocial effects and coping mechanisms of Covid-19 patients